Fantasies of Participation: The Situationist Imaginary of New Forms of Labour in Art and Politics - Grindon, Gavin (The Nordic Journal of Aesthetics, 2016)
The Situationist International (SI) have become a canonical reference point when discussing artists’ participation in political action or activism. This article attempts to decentre the SI from this position, by tracing their theories and representations of political agency and labour. I argue that their notion of agency is deeply conflicted, epitomized by the dual invocations ‘never work/all power to the workers’ councils. I examine how the SI’s representations of agency betray an attraction to and fascination with 1960s reactionary fantasies around brainwashing, conditioning, control and torture. Their practical descriptions of a constructed situation, which ‘makes people live’ are, in fact, closer to torturous state control than total liberation. The notions of agency they mobilise draw on colonial and classist sources, which actually deny the agency of radical movements. As a result, the SI produce a series of weak fantasies of participation, in which agency is denied and ‘demanding the impossible’ is actually a demand to constitute and police the impossible. Artistic-political agency was both guarded centre and constituent other. The SI’s policing of their identity, tied in name to the agency of ‘situations’, involved the ongoing exclusion and repression of other artists’ more practically-engaged labour within social movements.